How do chemical fertilizer reduction policies work? —Empirical evidence from rural china - Yang, Yurong; Li, Zhaoliang; Jin, Minghao (Frontiers in Environmental Science, 2022)
China has issued a series of policies to regulate the usage of chemical fertilizer. Are these policies effective? If so, how do they work? To answer the above questions, this study empirically analyzed the effects of different types of policies (regulatory, incentive, and publicity policies), as well as their internal mechanisms and the moderating role of farmers’ risk attitudes, on the usage of chemical fertilizers in agricultural production. We found that the policies and their interactions had positive significant effects on the reduction of chemical fertilizer usage while the influences of their interaction variables were the most statistically significant, and the relationships between the policies and reduction were negatively regulated by the risk attitudes of the surveyed farmers. Furthermore, the policies encouraged chemical fertilizer reduction by improving the farmers’ income expectations while the farmers’ risk attitudes negatively regulated the intermediary effects of their income expectations. This study enhances the understanding of the influence of economic rationality on individual decision-making, as postulated in neoclassical economics, to a certain extent. The conclusions are of much practical significance to the substantial reduction of chemical fertilizers and the green transformation of agriculture in China.